United States - Latin America and the Caribbean Trade Developments 2020 - NU. CEPAL (ECLAC, 2020)
United States Trade Developments 2020 provides an overview of selected developments in United States trade relations with Latin America and the Caribbean and of measures that inhibit the free flow of goods among countries in the Western Hemisphere. This is an annual report elaborated by the ECLAC Washington Office. This year’s report has a special focus on the effects of the COVID-19 pandemic on trade related issues. Specifically, it provides information on the early impact of the COVID-19 pandemic on U.S. trade and migration flows, supply chains as well as some of the restrictions to the movement of people, goods, services and foreign direct investment that were adopted in response to the pandemic.